Science in the ancient world : from antiquity through the middle ages - Lawson, Russell M., 1957- (ABC-CLIO, 2021)
"Explores the history of science in the ancient world from prehistory through roughly 1300 CE, looking not just at Greece and Rome but at developments in Africa, Asia, and the Americas as well"-- Provided by publisher.
Keywords: Science, Ancient -- Encyclopedias.; Science, Medieval -- Encyclopedias.; Sciences anciennes -- Encyclopédies.; Sciences médiévales -- Encyclopédies.; Science, Ancient; Science, Medieval; Encyclopedias